Penggunaan Media Wordwall dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran IPA SMP Negeri 1 Lebakwangi - Nurfarizki, Rifal; Mahpudin, Asep (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the research plan on improving students' learning motivation in Science subjects using Wordwall learning media. This study was conducted using the Quasi Experiment method and using the Nonequivalent Control Group Design. This study was located at SMP Negeri 1 Lebakwangi and involved two classes as research samples, namely class VII D with 34 students and class VII E with 34 students. The data collection technique in this study was using a questionnaire. The results of this study were that the average learning motivation of students in the class using Wordwall media (62.32) was higher than the class without Wordwall (38.88). This difference of 23.44 points was statistically significant (p = 0.000), which indicated that the use of Wordwall was effective in improving students' learning motivation in Science subjects at SMP Negeri 1 Lebakwangi. Based on the results of the Independent Samples T-Test.